THE ROLE OF COMMERCIAL BANKS IN FINANCING SMALL AND MEDIUM ENTERPRISES IN IRAQ (World Economics and Finance Bulletin, 2025)
This research aims to analyze the role of commercial banks in financing small and medium enterprises in Iraq, and to study the challenges facing this sector and their impact on financing projects. The policies and procedures followed by commercial banks to provide financing for small and medium enterprises will be analysed. The various financing methods available for small and medium enterprises in Iraq will be studied, and the impact of financing small and medium enterprises on economic growth in Iraq will be evaluated. The study sample consisted of (668) employees of Iraqi commercial banks in Baghdad. Where the researcher designed a research tool measuring the contribution of commercial banks. in the financing of small and medium-sized enterprises in Iraq, and data were statistically processed using the program of statistical analysis (SPSS), and it came out with the following results: 1- Commercial banks are considered one of the significant sources of finance for small and mediumsized enterprises in Iraq because the banks provide these projects with their needed financing and lending. 2- Commercial banks of Iraq are currently suffering from some problems related to capital and security weaknesses and political problems that play a significant role in their ability to finance small and medium-sized industries
Keywords: Commercial Banks; Financing